2001
DOI: 10.1021/bp000162z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Bioreactor Systems for the Production of High Titer Retroviral Vectors

Abstract: Improved, human-based packaging cell lines allow the production of high-titer, RCR-free retroviral vectors. The utility of these cell lines for the production of clinical grade vectors critically depends on the definition of optimal conditions for scaled-up cultures. In this work, a clone derived from the TE Fly GALV packaging cell (Duisit et al. Hum. Gene Ther. 1999, 10, 189) that produces high titers of a lacZ containing retroviral vector with a Gibbon Ape Leukemia Virus envelope glycoprotein was used. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 25 publications
2
69
0
Order By: Relevance
“…Kang et al (2000) showed that daily vector production was approximately 30 times greater in a packed bed bioreactor (packed with FibraCel discs) than a microcarrier system utilizing 3 g l À1 Cytodex. Similarly, Merten et al (2001a) showed a 116% increase in the maximum virus titer and a 400% increase in daily vector production when comparing a microcarrier system (5 g l À1 cytodex 1) and a CelliGen packed bed bioreactor containing 70 g of FibraCel discs. Evaluation of a fluidized bed bioreactor (Cytopilot) was recently carried out by .…”
Section: Bioreactor Designmentioning
confidence: 90%
See 4 more Smart Citations
“…Kang et al (2000) showed that daily vector production was approximately 30 times greater in a packed bed bioreactor (packed with FibraCel discs) than a microcarrier system utilizing 3 g l À1 Cytodex. Similarly, Merten et al (2001a) showed a 116% increase in the maximum virus titer and a 400% increase in daily vector production when comparing a microcarrier system (5 g l À1 cytodex 1) and a CelliGen packed bed bioreactor containing 70 g of FibraCel discs. Evaluation of a fluidized bed bioreactor (Cytopilot) was recently carried out by .…”
Section: Bioreactor Designmentioning
confidence: 90%
“…Production can be further enhanced through optimization of the culture conditions. Secondly, viruses are particles not small molecules, and have a very short half-life, typically 2-8 h at 37°C (Le Doux et al 1999;Merten et al 2001a). Maintaining their capability to infect target cells is essential.…”
Section: Retroviral Vectorsmentioning
confidence: 99%
See 3 more Smart Citations